The Uncertainty of Economic Policy: A Hinder for Financial Sustainability? - QIN Meng; SU Chi-Wei (Management of Sustainable Development)
Creating a favorable and robust national financial ecosystem represents a pivotal objective for China during its new phase of development. This article employs principal component analysis to quantify trends in financial vulnerability, condition, stability, pressure, and development, collectively serving as indicators of financial market performance. Following this, the article delves deeper into the influence of uncertainty in economic policy on financial market operations by leveraging the SVAR model. The research concludes that an increase in economic policy uncertainty (EPU) initially exacerbates the fragility of the financial market, causing significant volatility and impacting its stability negatively. However, China’s financial market possesses a self-regulation mechanism that gradually mitigates and transforms this impact over time. Notably, a positive shock to EPU can alleviate financial pressure in the short term by temporarily suppressing the vitality of the market. In addition, the overall rise in EPU hinders financial development. In summary, despite the market’s self-regulatory capacity, heightened EPU still hinders financial sustainability in China. Based on this research, it is recommended that China should strengthen policy coordination and predictability to promote financial sustainability.